Electrochemical impedance spectroscopy studies of the buffered and non‐buffered microbial fuel cell. Issue 2 (29th January 2023) - Nourbakhsh, Fatemeh; Mohsennia, Mohsen; Pazouki, Mohammad
Abstract: The positive effect of buffers to maintain a sui pH for microorganism growth and increase the electrolyte conductivity in microbial fuel cells (MFCs) encourages more studies on the development of new buffer solutions. The effect of types of biological buffers such as phosphate, tris, succinate, and maleate on power production in dual chamber MFC inoculated by saccharomyces cerevisiae has been examined. Electrochemical impedance spectroscopy has been used for evaluating the performance of the buffered and non‐buffered MFC systems. Considering the important impact of buffer type on the resistance of ion migration within the electrolyte and electron transport resistance of the cell components, the internal resistance of the MFC with different used buffers has been obtained and compared. According to the obtained results, the tris buffer solution showed a positive influence on the power output with a power density of 25.41% higher than phosphate.